Visitor profiling at the Museum of Human Evolution of Burgos (Spain) - Conforti, María Eugenia (2018)
This paper presents the first study ever conducted on the profile of visitors to the Museum of Human Evolution of Burgos (Spain), which exhibits the finds of the Atapuerca archaeo-paleontological sites. The research was guided by the principles of public communication of science and the methodology of the studies on museum visitors. The analysis reveals a positive perception; the Museum is associated with the sites and they are valued as cultural heritage. Complaints are very limited but useful to produce a set of recommendations to further improve the exhibition. In addition, the findings are placed in the context of similar research carried out at other museums in Spain.